2019
DOI: 10.1007/s40430-018-1555-0
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmotic flow of pseudoplastic nanoliquids via peristaltic pumping

Abstract: The study of electroosmotic flow of biorheological fluids has been employed in the advancement of diversified biomicrofluidics systems. To explore more in this field, a mathematical model is developed to investigate the electroosmotic flow of pseudoplastic aqueous nanoliquids in microchannel. A tangent hyperbolic fluid model is employed to describe the rheological behavior of the pseudoplastic fluid. Here, analytical solutions for potential distribution, temperature and nanoparticle fraction are derived and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Sharma et al delineated the analysis of double‐diffusive convection in electroosmosis‐regulated peristaltic transport of nanofluids. In another paper, Sheikholeslami studied the simulation for non‐Darcy nanofluid using the Lattice Boltzmann method. Some recent articles on flow with nanoparticles are (References ).…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al delineated the analysis of double‐diffusive convection in electroosmosis‐regulated peristaltic transport of nanofluids. In another paper, Sheikholeslami studied the simulation for non‐Darcy nanofluid using the Lattice Boltzmann method. Some recent articles on flow with nanoparticles are (References ).…”
Section: Introductionmentioning
confidence: 99%
“…Francesko et al [19] observed the progress of LOC and microfluidics in detail. Javavel et al [20] illustrated the EOF of pseudoplastic nano liquids through peristaltic pumping. However, the above studies did not examine the electroosmotic effects in peristaltically flowing third order fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, none of the studies focused on the combined effects of peristaltic and electroosmotic pumping processes to enhance performance efficiency of smart pumps for fulfilling the need of nanotechnology and health care. By addressing the dual benefits of both pumping mechanisms, several mathematical models [23][24][25][26][27] have been presented to analyze how electroosmosis controls/amplifies the peristaltic pumping process. Prakash and Tripathi [23] have studied radiative heat flux effects in electroosmotic driven peristaltic flow of Williamson viscoelastic ionic nanoliquids through microfluidic channels.…”
Section: Introductionmentioning
confidence: 99%
“…Prakash and Tripathi [23] have studied radiative heat flux effects in electroosmotic driven peristaltic flow of Williamson viscoelastic ionic nanoliquids through microfluidic channels. Prakash et al [24] examined the electro-osmotic driven peristaltic pumping of pseudoplastic nanofluid in a conduit.…”
Section: Introductionmentioning
confidence: 99%